2013 8th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2013
DOI: 10.1109/hri.2013.6483527
|View full text |Cite
|
Sign up to set email alerts
|

Towards empathic artificial tutors

Abstract: In this paper we discuss how the EMOTE project will design, develop and evaluate a new generation of artificial embodied tutors that have perceptive capabilities to engage in empathic interactions with learners in a shared physical space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The annotations were performed with two independent coders using the ELAN multimedia annotation tool. 3 In addition to this, pre-and post-test sheets were also graded by the coders. In terms of the reliability of the participants' behaviours, Cohen's kappa showed 0.84 of agreement for verbal behaviour, 0.92 for the gaze behaviour and 0.96 for the pre-and post-test sheet grading, indicating a good agreement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The annotations were performed with two independent coders using the ELAN multimedia annotation tool. 3 In addition to this, pre-and post-test sheets were also graded by the coders. In terms of the reliability of the participants' behaviours, Cohen's kappa showed 0.84 of agreement for verbal behaviour, 0.92 for the gaze behaviour and 0.96 for the pre-and post-test sheet grading, indicating a good agreement.…”
Section: Resultsmentioning
confidence: 99%
“…That study showed that robots can form relationships with children, and also that children may learn from robots as they learn from their peers. In addition, the EMOTE project (http://www.emote-project.eu/), a European project which aims to create a robotic tutor with empathic capabilities, is also exploring the role of robots as tutors to assist learners, specifically addressing the role of empathy in education [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Within the EMOTE project, the original online single player game was adapted to a multiplayer version where participants interact by using a multi-touch table or a tablet. This was done to stimulate collaborative learning [17], [4].…”
Section: Collaborative Learning Scenariomentioning
confidence: 99%
“…The project aims to design, develop and evaluate a new generation of virtual and robotic embodied tutors with perceptive capabilities to engage in empathic interactions with learners in a shared physical space. The work presented in this paper relates to the collaborative scenario in EMOTE: a gamebased learning environment related to Geography curriculum running on a multi-touch table [4], [5]. This learning environment is set apart from traditional Intelligent Tutoring Systems (ITS) in that the robot embodiment provides the system with the ability to demonstrate intention to interact and can make use of gaze, mutual eye contact and ostensive signals (e.g., posture) that have been shown to improve learning [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation